ВЛИЯНИЕ ТИРЕОИДНОЙ ДИСФУНКЦИИ НА ПСИХОЭМОЦИОНАЛЬНЫЙ СТАСУС ПАЦИЕНТОВ - Курбанов Дониёр Бахтиёрович,; Хажидедаева Назокатхон Али кизи,; Абдуллаева Зебохон Хамидулло кизи,; Жамолиддинов Нурмухаммад Жалолиддин оглы, (TADQIQOTLAR, 2025)
Abstract.  This  review  examines  psychoemotional  disorders  associated  with thyrotoxicosis  and  hypothyroidism,  including  anxiety,  depression,  and  cognitive impairments. It is noted that thyroid dysfunction has a significant impact on the central nervous system and may mask the somatic nature of the disease. Special attention is given  to  obsessive-phobic  symptoms,  asthenic  conditions,  hypothyroid encephalopathy,  and  evening  variability  in  psychoemotional  states. The  aim  of  the review is to summarize and analyze current scientific data on the relationship between thyroid dysfunction and psychoemotional disorders in order to raise awareness among physicians  of  various  specialties  about  the  importance  of  a  comprehensive, interdisciplinary approach to diagnosing and treating such patients. The literature used is primarily based on authoritative clinical guidelines, textbooks, and contemporary scientific publications.